Use of common carp (Cyprinus carpio) and Aeromonas salmonicida for detection of immunomodulatory effects of chemicals on fish. Issue 2 (30th November 2017) - Nakayama, Kei; Yamashita, Ryohei; Kitamura, Shin-Ichi
Abstract: To develop a test for assessing the immunomodulatory effects of chemical pollutants on fish, we evaluated the effects of dexamethasone on the natural host–pathogen interaction between common carp ( Cyprinus carpio ) and Aeromonas salmonicida . Carp were exposed to 1 mg L −1 dexamethasone for the entire experimental period. One week after the exposure test started, the exposed fish, as well as unexposed fish, were bath-infected with A. salmonicida . One hundred percent mortality was observed in bacteria-infected fish exposed to dexamethasone, whereas no infection-associated mortality was observed in infected fish in the absence of dexamethasone exposure. In a separate experiment, dexamethasone exposure significantly suppressed hemolytic complement activity in bacteria-infected fish. These results clearly indicate that exposure to a high concentration of dexamethasone suppressed the carp immune system and caused subsequent mortality. Thus, this proposed test method is likely to be useful for evaluating the immunomodulatory effects of chemicals in fish. Highlights: The effects of dexamethasone on a host–pathogen relationship were analyzed. Common carp was used as the host and A. salmonicida as the pathogen. Dexamethasone exposure increased the carp's susceptibility to bacterial infection.